2018
DOI: 10.1002/csr.1643
|View full text |Cite
|
Sign up to set email alerts
|

The impact of water information disclosure on the cost of capital: An empirical study of China's capital market

Abstract: This study seeks to understand the underlying relationship between water information disclosure and the cost of capital in Chinese high‐water risk firms. With continuous strengthening of the Chinese Government's water regulation policy, water resources have begun to affect the sustainable development of enterprises. Many stakeholders have begun to pay attention to a series of water resources issues that companies face. As an important means of transmitting signals between enterprises and capital markets, water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 70 publications
1
30
0
4
Order By: Relevance
“…The information content of voluntary disclosure was found to be reflected in changes in stock prices (Patell, 1976;Waymire, 1984;Ajinkya and Gift, 1984;Pownall and Waymire, 1989;and Lev and Penman, 1990). Moreover, voluntary disclosure was found to reduce the cost of equity (Botosan, 1997;Hail, 2002;Zhou et al, 2018) and increase the liquidity particularly in emerging markets (Schoenfeld, 2017;Haddad et al, 2009). It was also found that the disclosure of more valid, reliable and relevant information improves the accuracy of users' expectation and attracts the attention of analysts (Lang and Lundholm, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…The information content of voluntary disclosure was found to be reflected in changes in stock prices (Patell, 1976;Waymire, 1984;Ajinkya and Gift, 1984;Pownall and Waymire, 1989;and Lev and Penman, 1990). Moreover, voluntary disclosure was found to reduce the cost of equity (Botosan, 1997;Hail, 2002;Zhou et al, 2018) and increase the liquidity particularly in emerging markets (Schoenfeld, 2017;Haddad et al, 2009). It was also found that the disclosure of more valid, reliable and relevant information improves the accuracy of users' expectation and attracts the attention of analysts (Lang and Lundholm, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Water information disclosure is the core dependent variable. We used the “water information disclosure index” scale (see Appendix) as described in Zeng et al (2018) and Zhou et al (2018) to comprehensively reflect the water information disclosure of the listed companies. The scale consists of a qualitative index (15) and a quantitative index (12) for a total of 27 indicators.…”
Section: Methodsmentioning
confidence: 99%
“…Dengan nilai koefisien 0,026 (< 0,05), biaya lingkungan belum mampu memicu besarnya pengung kapan air. Temuan ini menunjukkan bahwa perusahaan masih belum baik dalam men jalankan good water governance (Ferreira et al, 2010;Zhou et al, 2018).…”
Section: Variabelunclassified
“…Pengungkapan air merupakan topik pe nelitian yang masih baru (Zhou et al, 2018). Penelitian ini membahas kepedulian peru sahaan dalam pengelolaan air.…”
unclassified